PWE-383 Defaecating proctography misses external rectal prolapse in 40% of cases. (22nd June 2015) - James, D; Penna, M; Bloemendaal, A; Prapasrivorakul, S; Hompes, R; Jones, O; Cunningham, C; Lindsey, I
Abstract : Introduction: External rectal prolapse (ERP) is a debilitating condition for which the only cure is surgical. There are several ways to diagnose ERP including clinical examination, defaecating proctography (DP), and examination under anaesthesia (EUA). In many cases, a diagnosis of ERP is made clinically. In our unit DP is undertaken routinely in order to aid characterisation of ERP and aiding in planning operative strategy, even when clinically evident. This affords the opportunity to evaluate DP against the gold standard of clinical assessment/EUA. The purpose of this study is to investigate the accuracy of DP in the diagnosis of ERP compared to EUA or clinical examination. Factors that may influence failure of DP in the detection of ERP are also explored. Method: Data were acquired from a prospectively collected database in a tertiary referral pelvic floor service. The search was limited to those patients referred with or having a final diagnosis of ERP. Patients were included in analysis if they underwent DP and clinical examination or EUA. The primary endpoint was accuracy of DP in the diagnosis of ERP compared to a definitive diagnosis reached either by clinical examination or ultimately at EUA. Factors explored to explain any discrepancy included age and anorectal physiological parameters including maximum resting pressure (MRP, mmH2 O) (Mann-Whitney U test, α=0.05). Results: 113 patients had a diagnosis of ERP between July 2007 and December 2013 (median age 64y, range 18–95y, 89% female). Of these patients, 67 underwent both DP and clinical examination/EUA. 27 (40%) had a diagnosis of ERP made only on clinical examination or EUA and not detected on DP. 2 (3%) had ERP detected on DP and not on EUA. In both of these cases, grade 4 prolapse was detected at EUA and ERP on DP. Median maximum resting pressure [range] was significantly higher in those in whom DP missed compared to showed ERP (43.5 [12–122] vs. 29.5 [6–122], p < 0 .05). There was no significant difference in other ARP parameters between the two groups. There was no difference in median age [range] between the two groups (62 [25–86] vs. 55 [22–80], p = 0 .29). Conclusion: This study demonstrates the limitation of DP in the diagnosis of ERP. DP should be used with caution to diagnose the aetiology of a prolapsing lump described by a patient but not demonstrable clinically. In such patients, EUA should be considered. Patients in whom DP did not detect ERP had higher maximum resting pressure. The corollary of this may be patient difficulty reproducing ERP at DP because of better underlying sphincter function. Patients may also fail to produce their ERP at DP due to embarrassment associated with undergoing this invasive study. Disclosure of interest: None Declared.